Variation of Open-Pit Waste Dump Specimens Under Effective Pressure Influence - Tovele, Gerson. S. V.; Han, Liu; Shu, Ji Sen (Frontiers in Earth Science, 2021)
The waste dump is a giant artificial loose pile body composed of the fine, medium, and coarse particle sizes and different mines waste dumps have different compositions. The overburden pressure and effective pressure are some of the issues in a waste dump, where if not well controlled will lead to a landslide. Landslide is a threat for the workers, the environment, and the equipment in the waste dump of open-pit mining, and to keep the slope stable and safe is the number one priority. The present study investigated effective pressure influencing porosity, void ratio, and permeability in the open-pit waste dump. To better understand its influence in waste dumping, seven different soil samples are subject to consolidation and permeability under consolidation laboratory tests. The test samples were subject to a pressure ranging from 100 to 1600 kPa. The result shows a relationship between effective pressure, void ratio, porosity, and coefficient of permeability and that dump height management and control is of great importance for a more safe and better waste dump environment.